PRE-MILLING FLEXIBLE FIXTURE REVIEW AND OPTIMISATION (International Journal of Food and Nutritional Sciences, 2022)
Proper workpiece position and limitation are necessary for machining. Fixtures hold the workpiece in place to provide accuracy, consistency, and repeatability. To enhance machining quality, the Workpiece Fixture System (WFS) reduces workpiece elastic deformation. Workpiece accuracy and shape are affected by elastic deformation. Even the most precise machinery was unable to tighten tolerances due to the elastic deformation of the workpiece. Much research is needed for deformation prediction and optimisation. Large-scale or batch production WFSs require the setup of workpieces and fixtures for machining. The goal of fixture layout design (FLD) is to minimise machining forces and maximise machining efficiency by carefully positioning clamps and locators around a workpiece. In order to reduce elastic deformation, the right FLD holds the workpiece against cutting forces. Correct locator and clamp placement is essential for FLDs. WFS FLD optimisation is necessary for low-cost, high-quality machining.